Youth Unemployment and Job Insecurity in Europe: Problems, Risk Factors and Policies - Christer Hyggen (Edward Elgar Publishing, 2019)
Providing original insights into the factors causing early job insecurity in European countries, this book examines its short- and long-term consequences. It assesses public policies seeking to diminish the risks to young people facing prolonged job insecurity and reduce the severity of these impacts. Based on the findings of a major study across nine European countries, this book examines the diverse strategies that countries across the continent use to help young people overcome employment barriers.